3D-ETFE: Development and evaluation of a new printed and spatially transformed foil improving shading, light quality, thermal comfort and energy demand for membrane cushion structures. (September 2017) - Cremers, Jan; Marx, Hannes
Abstract: Standard membrane structures using ETFE foils have a very high solar transmission (a single layer of typical transparent ETFE foil ≈ 93%). Regarding façade and roof applications this can result in serious problems with overheating and also cause a high degree of thermal discomfort and high cooling loads. The presented new shading approach is inspired by the widely used architectural idea of the shed roof (saw-tooth roof). Different geometry variants of a new spatial transformed foil have been manufactured in lab scale with the aim to quantify the cooling energy saving potential and the thermal comfort compared to a conventional system by using dynamic thermal simulations.